THE EFFECT OF PRESSURE VARIATIONS (3 KG, 4KG, 5 KG, 5.5 KG) AND MESH (30, 100) ON THE HARDNESS AND COMBUSTION VALUE OF CANDLECRON SHELL BRIQUETTE - De Jesus Moriera, Paulo; Tugur Redationo, Nereus; Crisanto Putra Mbulu, Bernardus (Universitas Katolik Widya Karya Malang, 2025)
Through this research there are two variables observed, namely the effect of variations in briquette charcoal pressure and specific heat value on the composition of carbonisation of hazelnut shell charcoal with tapioca adhesive on specific heat value. The initial process of research in the form of making charcoal on hazelnut shell briquettes, hazelnut shells are carbonised at 500 °, sieved with mesh 30 and 100 sieves, given a compressive load of 3 kg, 4 kg, 5 kg and 5.5 kg, the adhesive on hazelnut shell briquettes is starch and drying is carried out with a drying oven for 3 hours at a temperature of 80 °. The purpose of this study was to determine the effect of variations in pressure and particle size on the quality of hazelnut shell briquettes when viewed from the combustion rate and calorific value. The methodology used in the research is by using hazelnut shell briquette experiments, hazelnut shell briquette testing includes testing through hardness and briquette calorimeter bomb value. Through the research, it was found that the highest calorific value was in the 4 kg pressure specimen on mesh 30, namely 9221.09 cal/gram while the lowest combustion rate was produced by the hazelnut shell briquette specimen with a pressure of 5 kg and 5.5 kg, which was 4076.17 g/min. Giving different compressive loads and mesh sieves can provide advantages to briquettes including increasing specific calorific value, reducing water content and slowing the combustion rate